Kualitas Pelayanan Transportasi Umum pada Bus Batik Solo Trans (BST) Kota Surakarta - Braninda Caesarita Trisna Putri; Kristina Setyowati (Jurnal Mahasiswa Wacana Publik, 2022)
Surakarta City is one of the cities in Central Java which is densely populated, has high mobility, and has public transportation in the form of city buses, namely the Solo Trans Batik Bus (BST). Having a high level of congestion and transportation as the main means for activities, this study aims to determine the public's perception of the quality of services provided by the BST Bus. This study uses the service quality theory of Zeithaml, Parasuraman, and L. Berry which measures service quality with service quality dimensions (physical evidence, reliability, responsiveness, assurance, and empathy). The research method uses quantitative descriptive with data collection techniques, namely questionnaires distributed through google form. Data analysis uses Importance Performance Analysis which explains what performance factors must be provided by an organization to meet customer satisfaction. The results showed that the service quality of the BST Bus was categorized as very good because it had a fairly high level of conformity, namely 92.23%. In the cartesian diagram, most attributes are found in quadrant B where in this quadrant shows a high level of service performance in accordance with high consumer expectations as well.